Análise quantitativa e descritiva dos estabelecimentos da cidade de Lagoa D’anta - RN - Soares, Larissa Santos (Universidade Federal Rural do Semi-Árido, 2019)
Due to the significant increase in unemployment in the country in recent years, entrepreneurship has come to be seen as a solution for several people who find themselves without a source of income. Not only in the city of Lagoa d 'Anta, but in other cities of the state of Rio Grande do Norte, several types of enterprises are emerging and due to this, there was a lack of quantitative data on state entrepreneurs and enterprises, which ends up interfering in its economic development, since it will entail the impossibility of the emergence of new ventures. With this, the objective of this research is to present the characteristics of the enterprises and the profile of the entrepreneurs of the city of Lagoa d 'Anta. For the accomplishment of this work, we used a quantitative research, through preestablished questionnaires. With the data obtained through the questionnaires, the Excel tool was used to obtain the graphs and tables for the analysis of the results. This study was based on the project coordinated by Prof. Dr. Maristélio da Cruz Costa whose theme is "CHARACTERIZATION OF ENTREPRENEURSHIPS AND PROFILE OF ENTREPRENEURS IN THE MUNICIPALITIES OF THE STATE OF RN". In the characterization of entrepreneurship and profile of the entrepreneurs, it was possible to observe that in the municipality of Lagoa D 'Anta, women undertake more than men, the age group is 21 to 30 years old, and in relation to the educational level, many of them have completed high school. As for the enterprises, it was verified that a good part of them are young, the predominant sector is the commercial one, and they are relatively small businesses, since the majority considers themselves microentrepreneurs and they have up to 9 employees.
Monografia
Keywords: Empreendedorismo; Empreendimentos; Empreendedores; Desenvolvimento econômico; Entrepreneurship; Enterprises; Entrepreneurs; Economic development; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA